The Influence of Muamalah Fiqh, Compensation, and Religiosity on Fraudulent Behavior with Islamic Work Ethics as a Moderating Variable - Faisal, Yusuf; Sari, Egi Gumala; Artika, Artika; Athaillah, Ahmad (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2025)
Purpose: This study aims to obtain empirical evidence on the influence of fiqh muamalah, compensation and religiosity on fraudulent behaviour with Islamic work ethics as a moderation variable.Design/methodology: This study uses a quantitative type of research. This research was carried out using questionnaires distributed to lecturers and practitioners who are members of the Association of Islamic Economists (IAEI), the Sharia Economic Community (MES), the Forum of Lecturers in Islamic Economics and Business (FORDEBI) and the Indonesian Economics Scholars Association (ISEI), namely 350 questionnaires distributed via email and social media. Each questionnaire distributed has 114 statements to be answered by employees. From the distribution of the questionnaire carried out, 207 respondents were obtained who gave answers from 22 regions. To get the results of this study, the researcher used PLS SEM Version 3.0.Findings: The results of this study found that fiqh muamalah has a significant negative effect on fraudulent behaviour, compensation has a significant negative effect on fraudulent behaviour, religiosity has a significant negative effect on fraudulent behaviour, Islamic work ethics can moderate the relationship between fiqh muamalah and fraudulent behaviour, Islamic work ethics cannot moderate the relationship between compensation against fraudulent behaviour and Islamic work ethics cannot moderate the relationship between religiosity and fraudulent behavior.Practical implications: This research also encourages Islamic financial institutions to develop policies that foster a work environment rooted in Sharia principles, ultimately improving transparency, accountability, and trust in Islamic business practices.Originality/Value: This study focuses on fraudulent behaviour, where this research is a new research in discussing the relationship between fiqh mumalah and religiosity which is based on the nature of the Prophet.